Role of polysomnography in patients of snoring - Sachdeva, Saurav; Sharma, Karan; Kajal, Nirmal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: A useful working definition of snoring is the production of sound by the upper aero digestive tract during sleep. Polysomnography (PSG) is the monitoring of physiological parameters and physiological or pathological events in sleep. Methods: Fifty patients of either sex, having age >16 years were randomly selected from the ENT OPD based on the pre-determined inclusion and exclusion criteria. Subjective evaluation of snoring was done using Epworth sleepiness Scale. Neck circumference and body mass index were calculated in all patients. Then, complete local ENT examination was done including diagnostic nasal endoscopy. After that, full night polysomnography test of at least 6 hours duration was conducted. Results: Normal nasal endoscopy was seen in 64% of patients. DNS, DNS with ITH/MTH, ITH/MTH unilateral, ITH/MTH bilateral and nasal polyps were seen in 14%, 12%, 0%, 8% and 4% of patients respectively. Mean apnoea-hypopnoea index (AHI) was 6.58. 48% of the patients in our study had normal AHI (0-4). Mild, moderate and severe AHI was present in 44%, 6% and 2% of the patients respectively. Conclusions: All cases of snoring must be subjected to thorough clinical examination and nasal endoscopy and thereafter, be evaluated further for presence of sleep apnoea with polysomnography.